2021
DOI: 10.3354/cr01661
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impacts of climate change on industrial water demand by sector

Abstract: The impacts of climate change on industrial water demand (IWD) directly affect IWD management. In this study, we propose a framework for evaluating different impacts of climate change on IWD by sector, considering both direct and indirect effects. Data from 34 industrial sectors in Hebei Province, China, showed that the impacts of climate change varied by sector, and IWD in 22 of the 34 sectors was affected, ranging from -15.11 to 37.36% under the average rates of change in precipitation and temperature. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Jampanil showed that industrial water use in Thailand would increase by 0.2% in the mid-21st century due to climate change [30]. Zhang showed that climate change affects different sectors of industrial water use differently, with 22 of the 34 industrial water use sectors in Hebei Province being affected by rainfall and temperature change rates, with the changes ranging from −15.11% to 37.36% [31]. Wang constructed a statistical model to predict the changes in domestic water use in the Huaihe River basin based on the effects of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Jampanil showed that industrial water use in Thailand would increase by 0.2% in the mid-21st century due to climate change [30]. Zhang showed that climate change affects different sectors of industrial water use differently, with 22 of the 34 industrial water use sectors in Hebei Province being affected by rainfall and temperature change rates, with the changes ranging from −15.11% to 37.36% [31]. Wang constructed a statistical model to predict the changes in domestic water use in the Huaihe River basin based on the effects of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impacts of climate change, with the progress of the Sixth Coupled Model Intercomparison Project (CMIP6) conducted by the World Climate Research Programme, global climatologists have been able to share, analyze, and compare the latest global climate simulation results, providing direct support for current research on the impacts of climate change [10]. Based on the results of ScenarioMIP [11] experiments, a study on industrial water demand in Hubei Province, China, indicates varying impacts of climate change on different industries, ranging from −15.11% to 37.36% [12]. Furthermore, another study predicts the effects of climate change on industrial water demand in the Huai River Basin in China, suggesting a potential increase of 10% to 44.6% in water demand for industrial purposes [13].…”
Section: Introductionmentioning
confidence: 99%